2020
DOI: 10.31557/apjcp.2020.21.8.2331
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent BRCA1 Mutation, but no BRCA2 Mutation, in Vietnamese Patients with Ovarian Carcinoma Detected with Next Generation Sequencing

Abstract: Background: Identification of germline and somatic BRCA1/2 mutations in ovarian cancer is important for genetic counseling and treatment decision making with poly ADP ribose polymerase inhibitors. Unfortunately, data on the frequency of BRCA1/2 mutations in Vietnamese patients are scare. Methods: We aim to explore the occurrence of BRCA1/2 mutations in 101 Vietnamese patients with ovarian cancer including serous (n = 58), endometrioid (n = 14), mucinous (n = 24), and clear cell (n = 5) carcinomas. BRCA1/2 muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(18 reference statements)
1
3
0
Order By: Relevance
“…who used NGS to characterize all BRCA mutations in 101 Vietnamese patients with ovarian cancer. Their data showed that 6.9% (7/101) patients carried pathogenic mutations in BRCA1 and similar to our study, no BRCA2 mutation was identified ( 25 ). Another study in Vietnam involving 259 breast cancer patients reported only 2 carriers of BRCA mutations (0.8%) ( 26 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…who used NGS to characterize all BRCA mutations in 101 Vietnamese patients with ovarian cancer. Their data showed that 6.9% (7/101) patients carried pathogenic mutations in BRCA1 and similar to our study, no BRCA2 mutation was identified ( 25 ). Another study in Vietnam involving 259 breast cancer patients reported only 2 carriers of BRCA mutations (0.8%) ( 26 ).…”
Section: Discussionsupporting
confidence: 91%
“…The most prevalent BRCA1 mutation was NM_007294.3:c.5251C>T (p.Arg1751Ter) as identified in 3 unrelated individuals. This mutation was previously proposed to be a founder mutation in the Vietnamese when it was identified in 4% (4/101) patients with ovarian cancer in Vietnam ( 25 ). However, it has also been reported as a founder or recurrent mutation in the Greek ( 31 ) and Polish ( 32 ), making it a recurrent rather than founder mutation in the Vietnamese.…”
Section: Discussionmentioning
confidence: 98%
“…In a recent Vietnam report of Hoang Anh Vu (2020), there were four types of pathogenic BRCA1 mutations in Vietnamese patients with ovarian cancer. Among these patients, BRCA1 : c.1621C > T was present in two patients, BRCA1 : c.5251C > T in four patients and BRCA1 : c.5335delC in one case [ 4 ]. In a study of 200 cases of Asian origin on breast cancer patients living in the USA, three in four Vietnamese patients were identified with the mutation c.5251C > T in BRCA1 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients benefit from platinum based chemotherapy and targeted treatment with Poly (ADP-ribose) polymerase (PARP) inhibitors [ 2 ], while unaffected family members may benefit from genetic counseling for HBOC, thereby obtaining timely screening and reducing surgery such as prophylactic mastectomy or salpingo-oophorectomy [ 3 ]. Although two studies of BRCA1/2 gene mutations in the Vietnamese population were reported solely on patients themselves or in breast cancer [ 4 , 5 ], there have been no evidence on the mutations of these genes in HBOC patients. To date, there has been no official practice guideline for the diagnosis of HBOC syndrome in Vietnam; however, available national guidelines for the treatment of breast and ovarian cancer recommend target therapy for these patients with BRCA1/2 gene mutations.…”
Section: Introductionmentioning
confidence: 99%